Pathogenetic justification of sacubitril / valsartan use in respiratory-cardial comorbidity - T. V. Ashcheulova; K. M. Kompaniiets; N. M. Herasymchuk; I. V. Sytina (Patologìâ)
Among the comorbid conditions that significantly worsen quality of life and life expectancy are the chronic obstructive pulmonary disease and heart failure. Difficulties of drug therapy are the mutually exclusive approaches in the treatment of chronic obstructive pulmonary disease and concomitant cardiovascular pathology.